A phase 2 trial of dasatinib in patients with locally advanced or stage IV mucosal, acral, or vulvovaginal melanoma: A trial of the ECOG‐ACRIN Cancer Research Group (E2607). Issue 14 (23rd March 2017) - Kalinsky, Kevin; Lee, Sandra; Rubin, Krista M.; Lawrence, Donald P.; Iafrarte, Anthony J.; Borger, Darell R.; Margolin, Kim A.; Leitao, Mario M.; Tarhini, Ahmad A.; Koon, Henry B.; Pecora, Andrew L.; Jaslowski, Anthony J.; et al.
Abstract : BACKGROUND: KIT‐directed tyrosine kinase inhibitors such as imatinib have demonstrated benefits in KIT‐mutant (KIT+) mucosal, acral, vulvovaginal, and chronically sun‐damaged (CSD) melanoma. Dasatinib has superior preclinical activity in comparison with other tyrosine kinase inhibitors against cells with the most common KIT mutation, exon 11 L576P . The ECOG‐ACRIN E2607 trial assessed dasatinib in patients with these melanoma subtypes. METHODS: Patients received 70 mg of oral dasatinib twice daily. The primary objective for this 2‐stage phase 2 trial was response rate. Stage I was open to KIT+ and wild‐type KIT (KIT–) mucosal, acral, and CSD melanoma (n = 57). Stage II accrued only KIT+ tumors (n = 30). To enrich the trial for KIT+ tumors, vulvovaginal melanoma was added, and CSD melanoma was removed from eligibility. Secondary objectives included progression‐free survival (PFS), overall survival (OS), and safety. RESULTS: From May 2009 to December 2010, the first stage enrolled 57 patients. Among the evaluable patients, 3 of 51 (5.9%) achieved a partial response: all were KIT–. Stage II closed early because of slow accrual (November 2011 to December 2015). In stage II, 4 of 22 evaluable patients (18.2%) had a partial response; the median duration was 4.2 months. The median PFS was 2.1 months (n = 73; 95% confidence interval [CI], 1.5‐2.9 months). The median OS was 7.5 months (95% CI, 6.0‐11.9 months). In exploratory analyses, no differences were seen in PFS or OS with the KIT status or subtype. Dasatinib was discontinued because of adverse events in 9 of 75 patients (12%). CONCLUSIONS: The dasatinib response rate among KIT+ melanoma patients was low. In view of its clinical activity, it is recommended that imatinib remain the KIT tyrosine kinase inhibitor of choice for unresectable KIT+ melanoma. Cancer 2017;123:2688‐97 . © 2017 American Cancer Society . Abstract : In this multicenter, cooperative‐group, 2‐stage, single‐arm clinical trial, 7 of 73 evaluable patients (9.6%) with mucosal, acral, vulvovaginal, or chronically sun‐damaged melanoma achieved a partial response (wild‐type KIT, 3 of 42; KIT mutation, 4 of 25; and unknown KIT status, 0 of 6). The dasatinib response rate among KIT‐mutant melanoma patients is lower than anticipated.